Ice recrystallization inhibition of commercial kappa-, iota-, and lambda-carrageenans - KIRAN YILDIRIM, BERÇEM (ELSEVIER SCI LTD, 2021)
In this study, the structural composition of commercial kappa (kappa)-, iota (iota)-, lambda (lambda)-carrageenans was examined by using H-1 NMR spectroscopy, and the IRI activity of these different carrageenan samples was examined in sucrose solution. The H-1 NMR spectra showed that both lambda-carrageenans consist of kappa- and iota-units which are either present as a mixture of the two carrageenan types or as a kappa/iota-copolymer. According to the IRI activity results, kappa-carrageenan samples showed the highest IRI activity among the different carrageenans. In the presence of kappa-carrageenan, the round ice crystals transformed into a more angular and elongated shape, while this effect was less visible in the presence of the iota- and kappa-carrageenans. Viscosity measurements indicated that there is no correlation between the viscosity and the IRI activity of carrageenans. The IRI activities of the investigated carrageenans are different for the suppliers, and the results show that they are based on the structural differences and possibly also other compositional differences.
Keywords: Carrageenans; H-1 NMR spectroscopy; Ice crystal shape; Ice recrystallization inhibition; Viscosity; SCANNING-ELECTRON-MICROSCOPY; STRUCTURING PROTEINS; CREAM; CRYSTALLIZATION; TEMPERATURE; STORAGE; MECHANISMS; STABILIZER